Konstruksi Minat Belajar Anak pada Masyarakat Miskin di Desa Losari, Pacitan - Helmi Himawan Jauhar; Dian Tias Aorta (ANWARUL, 2026)
The issue of children’s low learning interest in poor communities has received attention in various previous studies, but research specifically discussing the social construction of learning interest in the context of interactions among economic, family, and social environmental factors remains limited. This study aimed to explore in depth the construction of children’s learning interest in poor communities in Losari Village. This study used a qualitative approach with a case study design, involving 15 participants consisting of school-age children, parents, and teachers selected through purposive sampling. Data were collected through in-depth interviews, field observations, and literature studies, and then analyzed using thematic analysis techniques. The results showed that children’s learning interest was significantly influenced by family economic conditions, which encouraged children to prioritize economic activities over formal education. In addition, low parental support, limited learning assistance, and negative perceptions of the benefits of education further reinforced low learning interest. Social environmental factors also played an important role in shaping children’s mindsets, particularly through peer influence and community norms that did not fully support educational continuity. These findings indicate that learning interest is a social construction formed through the interaction of structural and cultural factors, rather than merely an individual factor. The conclusion of this study emphasizes the importance of interventions that are not only economic but also social and cultural through strengthening the role of families and communities. The implications of this study are relevant for policymakers and educational institutions in designing strategies to increase educational participation that are systematic, contextual, and sustainable.